Severally Seeking Sartre. - O'Donohoe, B. P. (Cambridge Scholars Publishing, 2013)
This collection of twelve essays by scholars from the USA, Canada, the UK and Japan, presents fresh perspectives on familiar Sartrean subjects and novel approaches to neglected ones. Divided into four equal parts - Aesthetics, Philosophy, Politics and Revolt - its chapters reflect both the eclectic scope of Sartre's project and the dynamic attention it continues to attract. Moreover, this intellectual interest extends beyond the field of ""Sartre studies"" and across the generations, from estab ...